2022
DOI: 10.1021/acsomega.2c05658
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Evaluation of Emission and Performance Characteristics of Thumba Methyl Ester (Biodiesel)

Abstract: Thumba oil with a higher triglyceride content can be a promising feed for synthesizing a fatty acid alkyl ester as an alternative to pure diesel. The current study investigates the emission and performance characteristics of thumba methyl ester (TME) in compression ignition (CI) engines corresponding to variable loads and compression ratios (CRs), respectively. TME was prepared at an optimized pressure of 5 bar by hydrodynamic cavitation. The properties of TME–diesel blends with varied volume percentages of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(160 reference statements)
0
1
0
Order By: Relevance
“…5, 10, 15, 20, and 25) were compared with pure TME (Thumba methyl ester) and pure diesel. The results showed that the TME-diesel blends with 20% biodiesel had the lower emission and higher BTE [ 24 ]. In addition, Jatropha curcas oil was selected as a feedstock for biodiesel and blended with diesel fuel at 20%, 40%, 60%, 80%, and 100% by volume (B20, B40, B60, B80, and B100) to evaluate the performance, emission characteristics of diesel engines.…”
Section: Introductionmentioning
confidence: 99%
“…5, 10, 15, 20, and 25) were compared with pure TME (Thumba methyl ester) and pure diesel. The results showed that the TME-diesel blends with 20% biodiesel had the lower emission and higher BTE [ 24 ]. In addition, Jatropha curcas oil was selected as a feedstock for biodiesel and blended with diesel fuel at 20%, 40%, 60%, 80%, and 100% by volume (B20, B40, B60, B80, and B100) to evaluate the performance, emission characteristics of diesel engines.…”
Section: Introductionmentioning
confidence: 99%